Nilai Pendidikan Islam dalam Qur'an Surah Luqman Ayat 1-19: Tinjauan Kognitif, Afektif, dan Psikomotorik - Nurhadia Fitri; Mahsyar Idris (Madrasah Tsanawiyah DDI Cilellang, 2019)
The main focuses in this study are 1) Islamic educational values contained in QS Luqman/31: 1-9; 2) fostering cognitive, affective, and psychomotor potential according to QS Luqman/31: 1-9; and 3) the results of the development of cognitive, affective, and psychomotor potential according to QS Luqman/31: 1-9. This study is library research which is descriptive analysis using normative theological, historical, and pedagogical approaches. The results showed that the values of Islamic education in QS Luqman/31: 1-9 included tauhid education, moral education, worship education, social education, mental education, and exemplary education. The application of these educational values in the dimensions of cognitive, affective, and psychomotor is carried out by Luqman al-Hakim who is known to be virtuous, wise, intellectual, and true in words and deeds. The nature and attitude of the educator will produce students who have strong faith, good morals, and understanding of Shari'a by implementing it correctly as evidence of the development of balanced cognitive, affective, and psychomotor potentials.